Barriers in Disclosing Medication Mishaps at Public Sector Hospitals Nurses Perspectives - Memon, Khalida Naz; Abbas, Zeeshan; Sodho, Mahaveer Singh (Journal of Liaquat University of Medical & Health Sciences, 2021)
OBJECTIVES: To identify barriers to disclosing medication mishaps among study populations and the association between hiding medication mishaps to the population’s socio-demographic features. METHODOLOGY: This Descriptive cross-sectional study was carried out at Clinical & allied wards of Liaquat University Hospital (LUH) Jamshoro/Hyderabad, Sindh Govt Hospitals of Qasimabad, Peretabad & Kohsar, Shah Bhitai Hospital, Countenance Difference Fund (CDF) Hospital, Services Hospital & Sir Cowasjee Jehangir Institute of Psychiatry Hyderabad from October – December 2019. Through Nonprobability convenience sampling, 264 registered nurses were selected as per eligibility criteria. The data was analyzed using (SPSS) version 23.0. Registered nurses, both male and female, having at least six months’ experience of work in a designated hospital and having qualification diploma, BSc.N (Post R.N) or BSc.N and MSc.N were included in the study. RESULTS: Participants (31.7%) agreed of committing a medication mishap; 69.9% reported not to disclose these mishaps. Professional education had a significant relationship to hiding medication mishaps (p=0.003). Around 43.1% of participants agreed with the existence of a highly functional reporting system in hospitals for disclosure of medication mishaps (p=0.02). Nurses (47.2%) had a high interest in reporting medication mishaps; still showing insignificant association with the actual mishap reporting (p=0.67). CONCLUSION: The study covers the most available public sector hospitals showing one-third of the participants committing medication mishaps. The finding of this study highlights the need to minimize mishap practices and maximize their disclosure if the consequences of medication mishaps are to alleviated. KEY WORDS: Medication mishaps, Hospital Nurses, Barriers, Disclosure, Public sector.